Compreendendo o processo de alfabetização: a visão do alfabetizando - Onetta, Elenice (2016)
Much has been researched and discussed about the factors that are present in the education of youth and adults. Generally, we have access to the point of view of schools, teachers, and family; but less often, we hear the student as a subject in the school context. Therefore, we chose to understand the student's view, more specifically a student on her alphabetizing process, i.e., we decided to give voice, in this work, to a pupil about her career, using a systematic monitoring of a class of "Youth and Adult Education" (EJA) in a public school in the West Zone of São Paulo. To do so, we conducted a survey, which method is based on textual analysis using a qualitative approach, inspired by a reflective interview. Data analysis was based on the ideas of Paulo Freire (1921-1997), who considered school education as a possibility of reading and transforming the world and itself. The information that expressed the thoughts of the participant about her own alphabetizing process show that she was, as well as others, seeking this type of education, deprived of the possibility of education in childhood and adolescence because of the need to work. We can also say that she is part of a plunderer capitalist system and sustainer of social differences that segregates, excludes and marginalizes the masses, depriving them of access to adequate public school and devaluing the profession of educator. In this context, this type of education beckons to the population the possibility of liberation from its fears of dependence on others, which can be observed in the speech of our participant. We conclude that governmental actions are necessary in order to implement public policies to value the specificities of youth and adults as sociocultural protagonists with its own identity, class, gender, ethnicity and race, as well as the training of teachers that purport to act in the EJA